2019
DOI: 10.3390/nano9030461
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study of Hydrogen Storage in High-Entropy Alloy TiZrHfScMo

Abstract: In recent years, high-entropy alloys have been proposed as potential hydrogen storage materials. Despite a number of experimental efforts, there is a lack of theoretical understanding regarding the hydrogen absorption behavior of high-entropy alloys. In this work, the hydrogen storage properties of a new TiZrHfScMo high-entropy alloy are investigated. This material is synthesized successfully, and its structure is characterized as body-centered cubic. Based on density functional theory, the lattice constant, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Some new bcc structures of HEAs, such as FeCoNiMgTiZr, 102 FeMnNiCrAlW 103 and TiZrHfScMo, 109 were also investigated as hydrogen storage materials. Hu et al 109 used density functional theory (DFT) calculations to determine the structural parameters, View Article Online binding energy and formation enthalpy, as well as the electronic properties of hydrogenated TiZrHfScMo. The first-principles calculations indicated that the hydrogenation is a chemical sorption process, with the possibility of covalent bonding between the metal elements and hydrogen.…”
Section: Reviewmentioning
confidence: 99%
“…Some new bcc structures of HEAs, such as FeCoNiMgTiZr, 102 FeMnNiCrAlW 103 and TiZrHfScMo, 109 were also investigated as hydrogen storage materials. Hu et al 109 used density functional theory (DFT) calculations to determine the structural parameters, View Article Online binding energy and formation enthalpy, as well as the electronic properties of hydrogenated TiZrHfScMo. The first-principles calculations indicated that the hydrogenation is a chemical sorption process, with the possibility of covalent bonding between the metal elements and hydrogen.…”
Section: Reviewmentioning
confidence: 99%
“…The hydrogen storage properties of HEAs have attracted significant research interests recently [111,112]. In conventional research on hydrogen storage material, compositional selection is usually focused on transition metals such as Ti, V, Ni, and Zr, which are similar to compositions of HEMs [113].…”
Section: Hydrogen Storagementioning
confidence: 99%
“…Hence, most HEAs are not seen as promising hydrogen storage candidates. Another use of hydrogen atoms within metal lattices is for use as an indicator to present the difference of structure between HEAs and traditional alloys [112]. The presence of hydrogen in metallic systems also has an effect on mechanical properties, which is another important research direction to be conducted in the field of HEAs [114,115].…”
Section: Hydrogen Storagementioning
confidence: 99%
“…Recently, high entropy alloys (HEAs), which are composed of five or more elements with atomic concentrations of 5-35% and tend to form single-phase solid solutions [8][9][10][11][12][13][14][15], have received much attention in the hydrogen storage field [16][17][18][19]. A number of investigations have suggested that hydrogen storage properties of HEAs can be enhanced by carefully tuning their constituents [17] and an excellent hydrogen storage performance can be achieved, like high hydrogen storage capacity [19,20], reversibly phase transformation [21], rapid hydrogen absorption [22] and moderate absorption/desorption temperature and pressure [23].…”
Section: Introductionmentioning
confidence: 99%
“…Montero et al [32] reported that the addition of only 10% Ta into Ti 0.325 V 0.275 Zr 0.125 Nb 0.275 decreases the desorption temperature of the hydride phase by around 100 K. Despite these experimental studies of dehydrogenation of HEAs hydrides, few theoretical simulations of hydrogen desorption properties of HEAs have been reported. To date, there have been some theoretical calculations to study the hydrogen storage properties of HEAs, but most of them are mainly focused on the hydrogen absorption behavior [20,33]. Hence, it is necessary to investigate the underlying mechanism for the dehydrogenation of the HEAs on an atomic level.…”
Section: Introductionmentioning
confidence: 99%